2003
DOI: 10.1289/ehp.5838
|View full text |Cite
|
Sign up to set email alerts
|

Association between arsenic exposure from a coal-burning power plant and urinary arsenic concentrations in Prievidza District, Slovakia.

Abstract: To assess the arsenic exposure of a population living in the vicinity of a coal-burning power plant with high arsenic emission in the Prievidza District, Slovakia, 548 spot urine samples were speciated for inorganic As (As inorg ), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA), and their sum (As sum ). The urine samples were collected from the population of a case-control study on nonmelanoma skin cancer (NMSC). A total of 411 samples with complete As speciations and sufficient urine quality and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Arsenic levels in fingernailsWith respect to factors determining As levels in fingernails we found, even at the low environmental exposure levels close to the European average (Ranft et al, 2003), an association with As in soil, As in house dust and with the distance to the power plant. The influence of age (Table 4) should not be overinterpreted since our study population was of high age.…”
Section: As In Fingernails [µG/g] Urinary As (Asmentioning
confidence: 64%
See 4 more Smart Citations
“…Arsenic levels in fingernailsWith respect to factors determining As levels in fingernails we found, even at the low environmental exposure levels close to the European average (Ranft et al, 2003), an association with As in soil, As in house dust and with the distance to the power plant. The influence of age (Table 4) should not be overinterpreted since our study population was of high age.…”
Section: As In Fingernails [µG/g] Urinary As (Asmentioning
confidence: 64%
“…In this population-based case-control study, a nonmelanoma skin carcinoma excess risk was reported for environmental As exposure from power station emissions in the district of Prievidza, Slovakia (Pesch et al, 2002). Associations with environmental exposure were found for urinary As sum , the methylated species MMA and DMA but not for As inorg (Ranft et al, 2003). Here, we report the results on As analysis in fingernails and the comparison of As levels in fingernails with urinary As species.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations